Indirect Taxes on International Aviation - Strand, Jon (IMF Working Papers; Working Paper, 2006)
This paper examines the case for internationally coordinated indirect taxes on aviation (as a source of general revenue-not (necessarily) as a source of development finance). The case for such taxes is strong: the tax burden on international aviation is currently limited, yet it contributes significantly to border-crossing environmental damage. A tax on aviation fuel would address the key border-crossing externalities most directly; a ticket tax could raise more revenue; departure taxes face the least legal obstacles. Optimal policy requires deploying both fuel and ticket taxes. A fuel tax of 20 U.S. cents per gallon (10 percent, at today's fuel prices, corresponding to assessed environmental damage), or alternatively ticket taxes of 2.5 percent, would raise about USD 10 billion if imposed worldwide, and USD 3 billion if applied only in Europe.